Sustainable Construction - Yepes, Víctor; García-Segur, Tatiana (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Construction is one of the main sectors that generates greenhouse gases. This industry consumes large amounts of raw materials, such as stone, timber, water, etc. Additionally, infrastructure should provide service over many years without safety problems. Therefore, their correct design, construction, maintenance, and dismantling are essential to reducing economic, environmental, and societal consequences. That is why promoting sustainable construction has recently become extremely important. To help address and resolve these types of questions, this book explores new ways of reducing the environmental impacts caused by the construction sector, as well promotes social progress and economic growth. The chapters collect the papers included in the "Sustainable Construction" Special Issue of the Sustainability journal. The papers cover a wide spectrum of issues related to the use of sustainable materials in construction, the optimization of designs based con sustainable indicators, the life-cycle assessment, the decision-making processes that integrate economic, social, and environmental aspects, and the promotion of durable materials that reduce future maintenance.